IMPLEMENTASI EDUCATION TOURISM MOBILE LEARNING DALAM PROGRAM DESA WISATA EDUKASI DI DESA CISAAT KABUPATEN SUBANG PROVINSI JAWA BARAT - Ucu Cahyana; Rahmat Darmawan; Ari Apriyansa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
the effectiveness of educational tourism village activities in Cisaat Village, Subang Regency as a fostered village of the UNJ Research and Community Service Institute. The problems encountered in educational tourism activities in Cisaat village are as follows: 1) lack of information about educational tourism destinations and home stays in Cisaat village, 2) there is no guideline for educational tourism activities for participants, 3) tour guides who are members of in POKDARWIS in Cisaat village they have not been able to understand well in guiding educational tourism activities in Cisaat village, 4) educational tourism activities in Cisaat village have not utilized information technology. Based on these problems, the UNJ community service team is trying to apply one of the information technology media in the form of education tourism mobile learning. This media is based on a mobile learning platform using mobile phones as the main medium. The urgency of this community service activity is as an alternative effort to support government programs in increasing tourism and development programs in rural areas. The developed educational tourism tourism mobile learning media is an application that contains educational tourism activity material, videos of tourism activity activities, tourism games, animations, and scientific explanations of various educational tourism activity activities that are operated on smartphone devices. The method used in carrying out the community service program is in the form of Training, Focus Group Discussion (FGD), Mentoring, and Field Practice. The findings obtained in this community service activity are: 1) the educational tour guides in Cisaat Village are very enthusiastic about participating in training on the use, 2) the features and menus contained in the education tourism mobile learning media are very helpful to guides in educational tourism village activities, 3) features about educational tourism destinations and activities in media education tourism mobile learning attract educational tour participants to take part in the program, 4) media education tourism mobile learning can increase the effectiveness of educational tourism programs in Cisaat village, Subang Regency. Abstrak Program pengabdian masyarakat ini bertujuan untuk meningkatkan efektivitas kegiatan desa wisata edukasi di desa Cisaat Kabupaten Subang sebagai desa binaan Lembaga Penelitian dan Pengabdian kepada Masyarakat UNJ. Permasalahan yang dihadapi dalam kegiatan wisata edukasi di desa Cisaat adalah sebagai berikut: 1) kurangnya informasi tentang destinasi kegiatan wisata edukasi dan home stay yang ada di desa Cisaat, 2) belum ada panduan kegiatan aktivitas wisata edukasi bagi peserta, 3) pemandu wisata yang tergabung dalam POKDARWIS di desa Cisaat belum dapat memahami dengan baik dalam memandu aktivitas wisata edukasi di desa Cisaat, 4) kegiatan wisata edukasi di desa Cisaat belum memanfaatkan teknologi informasi. Berdasarkan permasalahan tersebut, maka tim pengabdian masyarakat UNJ berupaya untuk menerapkan salah satu media teknologi informasi dalam bentuk bentuk education tourism mobile learning. Media ini berbasis platform mobile learning dengan menggunakan handphone sebagai media utamanya. Urgensi kegiatan pengabdian kepada masyarakat ini adalah sebagai salah upaya alternatif untuk mendukung program pemerintah dalam meningkatkan program pariwisata dan pembangunan di pedesaaan. Media education tourism mobile learning yang dikembangkan merupakan aplikasi yang berisi materi kegiatan wisata edukasi, video aktivitas kegiatan wisata, game wisata, animasi, dan penjelasan ilmiah dari berbagai aktivitas kegiatan wisata edukasi yang dioperasikan pada perangkat telepon pintar. Metode yang digunakan dalam menjalankan program pengabdian masyarakat adalah dalam bentuk Pelatihan, Focus Group Discussion (FGD), Pendampingan, dan Praktek Lapangan. Temuan yang diperoleh dalam kegiatan pengabdian kepada masyarakat ini adalah: 1) pemandu wisata edukasi di desa cisaat sangat antusias dalam mengikuti pelatihan penggunaan, 2) fitur dan menu yang terdapat dalam media education tourism mobile learning sangat membantu pemandu dalam kegiatan desa wisata edukasi, 3) fitur tentang destinasi wisata edukasi dan aktivitas dalam media education tourism mobile learning menarik minat peserta wisata edukasi untuk mengikuti program tersebut, 4) media education tourism mobile learning dapat meningkatkan efektivitas program wisata edukasi di desa Cisaat Kabupaten Subang.